2018
DOI: 10.1016/j.heliyon.2018.e00852
|View full text |Cite
|
Sign up to set email alerts
|

Yearning predicts subgenual anterior cingulate activity in bereaved individuals

Abstract: Complicated grief, or persistent complex bereavement disorder, is a condition that affects approximately 10% of bereaved individuals and is marked by intense longing and yearning for the deceased. Little is known about the neurocognitive mechanisms contributing to this syndrome, but previous research suggests that reward pathways in the brain may play a role. Twenty-five older adults were categorized based on grief severity into one of three groups: complicated grief (CG), non-complicated grief (NCG) and non-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The authors proposed that sgACC activation is associated with a stressful grief experience, though PGD was not assessed. A later study by McConnell et al (2018) observed no significant differences in sgACC activation between those with PGD and those without. However, in a symptomspecific analysis of all bereaved participants, the authors found that yearning (as assessed by the yearning item in the ICG) was associated with activation in the sgACC, independent of other ICG items or total score (O'Connor et al 2018).…”
Section: Cingulate Cortexmentioning
confidence: 85%
See 3 more Smart Citations
“…The authors proposed that sgACC activation is associated with a stressful grief experience, though PGD was not assessed. A later study by McConnell et al (2018) observed no significant differences in sgACC activation between those with PGD and those without. However, in a symptomspecific analysis of all bereaved participants, the authors found that yearning (as assessed by the yearning item in the ICG) was associated with activation in the sgACC, independent of other ICG items or total score (O'Connor et al 2018).…”
Section: Cingulate Cortexmentioning
confidence: 85%
“…The NAc co-activated with areas associated with pain, such as the insula and periaqueductal grey, prompting O' Connor et al (2008) to suggest that "craving" for the deceased was experienced as an affliction, as in addiction. A subsequent study attempted to replicate this finding with an older sample, but found no significant difference in NAc activation between PGD and non-PGD groups (McConnell et al 2018). The authors suggested this null finding may have been due to a small sample size or to the age of the subjects (the average age was 71 years, as opposed to 44 years in their 2008 paper), citing non-human animal research that shows a decline in certain NAc activity with advancing age (Ruegsegger et al 2017).…”
Section: The Basal Gangliamentioning
confidence: 94%
See 2 more Smart Citations
“…This under‐stimulation could in the long run even be related to the symptoms of PGD/PCBD. Additionally, studies investigating neural correlates of social loss indicate grief‐related altered activation in brain areas such as the NAcc 112 and the ACC, 113 which are associated with the reward‐system and high OT receptor densities. However, endogenous OT mechanisms in the central nervous system cannot be measured in the human living brain so far, which limits the possibilities to test for direct involvement of OT in the grieving process.…”
Section: Discussionmentioning
confidence: 99%